Novel cooperative caching strategies for video streaming distribution based on reconfiguration routers - Zhi-cong HE; Guang-zhao GU; Xin WANG; Jin ZHAO; Xiang-yang XUE (Tongxin xuebao)
A novel cooperative caching scheme based on reconfiguration routers was proposed to accelerate the delivery of streaming media.Through cooperative caching for popular videos among the routers,the server capability,especially bandwidth requirements were decreased.Moreover,the traffic over the backbone network was dramatically reduced and user experience was also improved due to the edge routers providing services for the user quickly.Furthermore,implemented a prototype system is implemented to evaluate the scheme,and the results show great improvement over the state-of-the-art solutions.